(untitled) (Melayu: Jurnal Antarabangsa Dunia Melayu, 2020)
The Keris is a short-bladed dagger considered to be the traditional weapon of the Malays. The dagger known as "keris Taming Sari" is the weapon of Hang Tuah in Hikayat Hang Tuah. This Keris is not only a traditional Malay weapon but also a symbol of Malay culture. However, there have not been any systematic studies about the keris Taming Sari. Based on the cultural studies of Edgar H. Schein, Taming Sari can be seen as a cultural organization with a layered structure. Each cultural layer has a specific meaning. The first layer is the artifact layer and the second layer is the value layer; both of these are obvious or explicit. However, the third layer is hidden or unseen. For this, it is necessary to use Roland Barthes’s semiotics approach. Two codes have been selected, namely the symbolic code and the cultural code, to interpret the meanings within this third layer. This study finds that in the first layer, keris Taming Sari has a form that consists of the hilt, sheath and blade. In the second layer, the usage value is evident, as keris Taming Sari is a weapon and a gift. By using the symbolic code, this third layer of Taming Sari reveals magical and miraculous values, while the cultural code reveals that the third layer indicates two underlying beliefs: animism and feudalism. The three cultural layers together give keris Taming Sari its own identity as a cultural artifact in Malay culture Keywords: Hikayat Hang Tuah, keris Taming Sari, cultural layers, codes